2007
DOI: 10.1021/np068044u
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Chemopreventive Effects of Cycloartane-Type and Related Triterpenoids in in Vitro and in Vivo Models

Abstract: Forty-eight natural and semisynthetic cycloartane-type and related triterpenoids have been evaluated for their inhibitory effects on Epstein-Barr virus early antigen (EBV-EA) activation induced by the tumor promoter 12-O-tetradecanoylphorbol-13-acetate (TPA) in Raji cells as a primary screening test for anti-tumor promoters. In addition, these triterpenoids have been tested for their inhibitory effects on activation of (+/-)-(E)-methtyl-2-[(E)-hydroxyimino]-5-nitro-6-methoxy-3-hexemide (NOR 1), a nitric oxide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 26 publications
1
27
0
Order By: Relevance
“…The protocols of assay of melanin content, in vitro EBV-EA activation experiment, determination of DPPH free-radical-scavenging activity, assay of TPA-induced ear-edema inflammation in mice, cytotoxicity assay, Annexin V-propidium iodide (PI) double staining, and Western blot analysis Akihisa et al, 2006Akihisa et al, , 2007Akihisa et al, , 2010aKikuchi et al, 2007Kikuchi et al, , 2011Tabata et al, 2005) were described in Supplementary data (S2).…”
Section: Biological Evaluationmentioning
confidence: 99%
“…The protocols of assay of melanin content, in vitro EBV-EA activation experiment, determination of DPPH free-radical-scavenging activity, assay of TPA-induced ear-edema inflammation in mice, cytotoxicity assay, Annexin V-propidium iodide (PI) double staining, and Western blot analysis Akihisa et al, 2006Akihisa et al, , 2007Akihisa et al, , 2010aKikuchi et al, 2007Kikuchi et al, , 2011Tabata et al, 2005) were described in Supplementary data (S2).…”
Section: Biological Evaluationmentioning
confidence: 99%
“…Furthermore, it is now also known that the major triterpenoids of Sutherlandia are structurally closely related to cycloartane-type triterpenoids with proven cancer chemopreventive activity (Kikuchi et al, 2007).…”
Section: Cancermentioning
confidence: 99%
“…The possibility that canavanine is not the only active compound is supported by Kikuchi et al (2007), who studied the cancer chemopreventive activity of 48 natural and semisynthetic cycloartane-type triterpenoids. Many of the compounds (so-called astragalosides) are known from the genus Astragalus L., also a member of the tribe Galegeae and related to Sutherlandia.…”
Section: Cancermentioning
confidence: 99%
“…Other biologically active compounds of interest are flavonol glycosides and triterpenoid saponins including the discovery of four new cycloartane glycosides, sutherlandiosides A-D, as well as SU1 which is the major triterpene in commercial Sutherlandia material (Fu et al, 2008;Van Wyk and Albrecht, 2008). Kikuchi et al (2007) demonstrated that cycloartane-type triterpenoids with a hydroxy group at C-24 in the side chain are possible chemopreventive agents in chemical carcinogenesis (Kikuchi et al, 2007). Sutherlandiosides A-D as well as SU1 have a hydroxyl moiety at the C-24 position, thus it would be of great interest to test these compounds for biological activity (Fu et al, 2008;Van Wyk and Albrecht, 2008).…”
Section: Introductionmentioning
confidence: 99%